الشيخ عثمان عبدالعزيز، ومنهجه في علم أصول الفقه من خلال رسالته الأصوليّة: (الأسئلة والأجوبة) - محمّد, ڕێناس حسن محمّدحسن (Sulaimani Journal for Humanities, 2023)
The core and the principle thought l of this study was to discuss the efforts, worldview and thought of Mullah Osman Abdulaziz, about one of the most sensitive and important issues related to the Holy Qur'an, which is the science of the principles of Fiqh. Obviously, Mullah Osman Abdulaziz has his own efforts and opinions in this field and due to his research on the science of the principles of Fiqh, he has come to have his own opinions in this field Book: (الأسئلة والأجوبة، في علم أصول الفقه) Then the views of Shaykh 'Uthman Abdul Aziz on the definition of the science of the principles of Fiqh, his method in the definition of legitimate rules, his thought on the level of evidence of consensus as legitimate evidence, and following science the principles of Fiqh and how to resolve contradictions in his worldview are briefly discussed and explained. Obviously, the subject of the scientific terms of the principles of Fiqh has many branches, from the definition of the science, to its forms, parts, conditions and types, but in general scholars have many differences in their understanding. However, there are many issues in the science of the principles of Fiqh that are agreed upon by the scholars. All these issues and their branches have been discussed in this short paper, and the evidence in the science of the principles of Fiqh has been cited for this issue. All these are the subjects of this paper.